EGFL7 participates in regulating biological behavior of growth hormone–secreting pituitary adenomas via Notch2/DLL3 signaling pathway. Issue 7 (July 2017) - Wang, Jianpeng; Liu, Qian; Gao, Hua; Wan, Dehong; Li, Chuzhong; Li, Zhaojian; Zhang, Yazhuo
Growth hormone–secreting pituitary adenoma accounts for about 20% of the third most common intracranial neoplasm—pituitary adenomas—which makes up 15% of all intracranial tumors. The growth hormone–secreting pituitary adenoma invasion is a key risk factor associated with the operation results and highly correlated with the clinical prognosis. The epidermal growth factor–like domain multiple 7 protein, a unique 29 kDa secreted angiogenic factor, can result in pathologic angiogenesis and enhance the tumor migration and invasion. In this study, for the first time we found that epidermal growth factor–like domain multiple 7 protein expression was markedly higher in invasive growth hormone–secreting pituitary adenoma than non-invasive growth hormone–secreting pituitary adenoma. The tumor volume, histologic subtypes, invasiveness and recurrence of growth hormone–secreting pituitary adenoma were significantly associated with epidermal growth factor–like domain multiple 7 protein expression. Furthermore, we discovered that the histological classification methods of growth hormone–secreting pituitary adenoma according to electron microscopic examination and biological marker classification methods according to epidermal growth factor–like domain multiple 7 protein expression are more valuable in clinical application than the traditional classification methods based on Knosp and Hardy-Wilson grades. In summary, our results indicated epidermal growth factor–like domain multiple 7 protein participates in growth hormone–secreting pituitary adenoma proliferation and invasion regulation via Notch2/DLL3 signaling pathway. These findings raised the possibility that epidermal growth factor–like domain multiple 7 protein might serve as a useful biomarker to assess growth hormone–secreting pituitary adenoma invasion and prognosis or a potential therapeutic target for growth hormone–secreting pituitary adenoma treatment.